Rasio Triglyceride / High Density Lipoprotein-Cholesterole dan Resistensi Insulin sebagai Faktor Risiko Diabetes Melitus Tipe 2 - Jefri Sandika (MAJORITY, 2020)
Diabetes mellitus (DM) is a metabolic disease that occurs due to abnormal insulin secretion, abnormal working insulin or both. One of the risk factors for DM is insulin resistance, which is the inability of insulin to perform the function of uptake and glucose utilization. The second most common cause of type 2 diabetes is dyslipidemia, or which is called diabetes dyslipidemia. In dyslipidemia there is an increase or decrease in plasma lipid fractions. Lipid fractions that play a role in the pathogenesis of DM are triglycerides (TG) and high density lipoprotein (HDL). Triglycerides are lipid fractions consisting of three fatty acid molecules, which are produced from free fatty acids (FFA) in the liver and some in the intestine. High-density lipoproteins are complex metabolic systems that has function as macrophages to remove cholesterol from artery walls. One examination that can be an indicator of insulin resistance is the ratio of triglycerides and high density lipoprotein cholesterole (HDL-C) levels. Measurements were made by dividing the concentration of TG with HDL-C, with the TG/HDL-C ratio having a risk is more than 3. The relationship between the TG/HDL-C ratio and the incidence of Type 2 DM is estimated to be due to β cell dysfunction. The TG/HDL-C ratio is used as a marker of β cell lipotoxicity which results in a decrease in insulin secretion and an increase in β cell apoptosis due to increased triglyceride concentrations. Hypertriglyceridemia and low levels of HDL indicate the occurrence of diabetes dyslipidemia.